High incidence of severe pain is associated with low opioid availability in patients with advanced cancer: a nationwide questionnaire survey in Japan. (July 2022) - Hasegawa-Moriyama, Maiko; Hara, Erina; Konishi, Mitsuru; Abe, Hiroaki; Uchida, Kanji; Sumitani, Masahiko
Abstract: Background: Opioid availability for the palliative care of patients with advanced cancer is increasing globally. However, opioid consumption in Japan is still extremely low compared with that in other countries. We investigated the current situation of pain control and opioid consumption in patients with advanced cancer in Japan. Methods: This was a national cohort study done in Japan after approval by the ethical committee of our institute the University of Tokyo Hospital (reference 202176NI). Between Sept 1, 2021, and Nov 15, 2021, caregivers from 2000 comprehensive support centres nationwide answered the web-based questionnaire survey asking for details about their assigned patients who died of end-stage cancer. The survey included the questionnaire of pain intensity and opioid prescription. Findings: Data from 1034 responders were retrieved, of which 1000 completed questionnaires for patients who died of end-stage cancer were considered valid. Of answers (excluding "I don't want to answer", "unknown", and "not applicable"), 254 (38%) of 665 patients complained of severe-to-intolerable cancer-related pain. Opioids were only available for 486 (77%) of 633 patients. The opioid adequacy rate, as defined by WHO, was negatively correlated with severe to intolerable pain (p=0·037). Only 344 (47%) of 730 patients with advanced cancer were supported by palliative care specialists. Interpretation: Pain control for advanced cancer pain is insufficient in Japan. In comparison with worldwide levels, opioid prescription is underused in clinical practice. The low availability of opioids can be improved by introduction of quality palliative care support for patients with advanced cancer. Funding: This study was funded by the authors and by Shionogi (Osaka, Japan), Nippon Zoki Pharmaceutical (Osaka, Japan), and Heartfelt (Kumamoto, Japan).